Skin repair and immunoregulatory effects of myeloid suppressor cells from human cord blood in atopic dermatitis - Kim, Chang-Hyun; Hong, Seung-Min; Kim, Sueon; Yu, Jae Ik; Jung, Soo-Hyun; Bang, Chul Hwan; Lee, Ji Hyun; Kim, Tai-Gyu (Frontiers in Immunology, 2024)
Introduction: Previously, we achieved large-scale expansion of bone marrow-derived suppressor cells (MDSCs) derived from cluster of differentiation (CD)34+ cells cultured in human umbilical cord blood (hUCB) and demonstrated their immunomodulatory properties. In the present study, we assessed the therapeutic efficacy of hUCB-MDSCs in atopic dermatitis (AD). Methods: Dermatophagoides farinae (Df)-induced NC/Nga mice (clinical score of 7) were treated with hUCB-MDSCs or a control drug. The mechanisms underlying the therapeutic effects of hUCB-MDSCs were evaluated. Results and Discussion: hUCB-MDSCs demonstrated immunosuppressive effects in both human and mouse CD4+ T cells. hUCB-MDSCs significantly reduced the clinical severity scores , which were associated with histopathological changes, and reduced inflammatory cell infiltration, epidermal hyperplasia, and fibrosis. Furthermore, hUCB-MDSCs decreased the serum levels of immunoglobulin E, interleukin (IL)-4, IL-5, IL-13, IL-17, thymus- and activation-regulated chemokines, and thymic stromal lymphopoietin. Additionally, they altered the expression of the skin barrier function-related proteins filaggrin, involucrin, loricrin, cytokeratin 10, and cytokeratin 14 and suppressed the activation of Df-restimulated T-cells via cell–cell interactions. hUCB-MDSCs promoted skin recovery and maintained their therapeutic effect even after recurrence. Consequently, hUCB-MDSC administration improved Df-induced AD-like skin lesions and restored skin barrier function. Our findings support the potential of hUCB-MDSCs as a novel treatment strategy for AD.